Proteomic Analysis of the Hemolymph After Metschnikowia bicuspidata Infection in the Chinese Mitten Crab Eriocheir sinensis - Jiang, Hongbo; Bao, Jie; Xing, Yuenan; Feng, Chengcheng; Li, Xiaodong; Chen, Qijun (Frontiers in Immunology, 2021)
The “milky disease” of the Chinese mitten crab, Eriocheir sinensis, is a highly lethal fungal disease caused by Metschnikowia bicuspidata infection. To elucidate the immune responses of the hemolymph of E. sinensis to M. bicuspidata infection, a comparative analysis of the hemolymph of E. sinensis infected with M. bicuspidata and that treated with phosphate buffered saline was performed using label-free quantitative proteomics. A total of 429 proteins were identified. Using a 1.5-fold change in expression as a physiologically significant benchmark, 62 differentially expressed proteins were identified, of which 38 were significantly upregulated and 24 were significantly downregulated. The upregulated proteins mainly included cytoskeleton-related proteins (myosin regulatory light chain 2, myosin light chain alkali, tubulin α-2 chain, and tubulin β-1 chain), serine protease and serine protease inhibitor (clip domain-containing serine protease, leukocyte elastase inhibitor, serine protein inhibitor 42Dd), catalase, transferrin, and heat shock protein 70. Upregulation of these proteins indicated that phenoloxidase system, phagocytosis and the ROS systems were induced by M. bicuspidata. The downregulated proteins were mainly organ and tissue regeneration proteins (PDGF/VEGF-related factor protein, integrin-linked protein kinase homing pat-4 gene) and hemagglutination-associated proteins (hemolymph clottable protein, hemocyte protein-glutamine gamma-glutamyltransferase). Downregulation of these proteins indicated that M. bicuspidata inhibited hemocyte regeneration and hemolymph agglutination. Fifteen differentially expressed proteins related to immunity were verified using a parallel reaction monitoring method. The expression trend of these proteins was similar to that of the proteome. To the best of our knowledge, this is the first report on the proteome of E. sinensis in response to M. bicuspidata infection. These results not only provide new and important information on the immune response of crustaceans to yeast infection but also provide a basis for further understanding the molecular mechanism of complex host pathogen interactions between crustaceans and fungi.